2019
DOI: 10.1017/ice.2019.180
|View full text |Cite
|
Sign up to set email alerts
|

Impact of multiple concurrent central lines on central-line–associated bloodstream infection rates

Abstract: Background:The current methodology for calculating central-line–associated bloodstream infection (CLABSI) rates, used for pay-for-performance measures, does not account for multiple concurrent central lines.Objective:To compare CLABSI rates using standard National Healthcare Safety Network (NHSN) denominators to rates accounting for multiple concurrent central lines.Design:Descriptive analysis and retrospective cohort analysis.Methods:We identified all adult patients with central lines at 2 academic medical ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Regarding COVID-19 specifically, international studies suggest that the choice of puncture site should be in the infraclavicular region to reduce exposure to oral and tracheal fluids, avoiding catheter-related infections; however, these sites increase the risk of pulmonary complications of mechanical ventilation ( 7 - 8 ) . An US cohort study observed that the risk of CLABSI increases proportionally to the number of lumens in the device ( 17 ) . Our study found that the majority of catheters were double lumen (96.4%) inserted into the jugular (80%).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding COVID-19 specifically, international studies suggest that the choice of puncture site should be in the infraclavicular region to reduce exposure to oral and tracheal fluids, avoiding catheter-related infections; however, these sites increase the risk of pulmonary complications of mechanical ventilation ( 7 - 8 ) . An US cohort study observed that the risk of CLABSI increases proportionally to the number of lumens in the device ( 17 ) . Our study found that the majority of catheters were double lumen (96.4%) inserted into the jugular (80%).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts at estimating the increase in CLABSI risk due to CVC concurrence have been made by others. 15,[31][32][33][34] Our estimates are lower than those observed in single medical center study from 2014 by Concannon et al 33 that quantified the attributable risk; however, the size of the study was smaller, and more importantly, it approached risk adjustment differently. Concannon et al 33 used more traditional logistic regression adjusting for markers associated with disease severity.…”
Section: Figure Time Tomentioning
confidence: 99%
“…Other investigators have demonstrated the varied effects of counting total CLD would have on CLABSI rates. 15,34,35 Based on these studies, the effect of comparing CLABSI rates using NHSN CLDs vs total CLDs appears to depend on the frequency of concurrent CVC use in the study population and the definition of concurrence (eg, any overlap at single time of day, at least several hours of overlap, entire days of overlap). Although simply counting all CLDs may be a simple approach to improving risk adjustment, it may not be the best approach.…”
Section: Figure Time Tomentioning
confidence: 99%
“…Dube et al 3 are not the first to measure the risk of CLABSI among patients with concurrent catheters; others have also found that concurrent catheters are independently associated with increased CLABSI risk (Table ). [3][4][5][6][7][8][9] Regarding surveillance, adding concurrent CVC days to the denominator reduces the measured incidence of CLABSI. Concurrent CVC days are not accounted for in the US…”
mentioning
confidence: 99%
“…Dube et al are not the first to measure the risk of CLABSI among patients with concurrent catheters; others have also found that concurrent catheters are independently associated with increased CLABSI risk (Table). Regarding surveillance, adding concurrent CVC days to the denominator reduces the measured incidence of CLABSI. Concurrent CVC days are not accounted for in the US Centers for Disease Control and Prevention National Healthcare Safety Network; this may partially explain the higher incidence of CLABSI in some tertiary-care academic centers.…”
mentioning
confidence: 99%